2022
DOI: 10.1016/j.xhgg.2021.100074
|View full text |Cite
|
Sign up to set email alerts
|

Novel pathogenic variants and quantitative phenotypic analyses of Robinow syndrome: WNT signaling perturbation and phenotypic variability

Abstract: Summary Robinow syndrome (RS) is a genetically heterogeneous disorder with six genes that converge on the WNT/planar cell polarity (PCP) signaling pathway implicated ( DVL1 , DVL3 , FZD2 , NXN , ROR2 , and WNT5A ). RS is characterized by skeletal dysplasia and distinctive facial and physical characteristics. To further explore the genetic heterogeneity, paralog co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 80 publications
4
42
0
Order By: Relevance
“…The phenotypes are ordered by dendrogram shown on the left based on hierarchical agglomerative clustering (HAC) analysis. A prevalence key is provided on the right This is in accordance with our recent phenotypic analysis of dominant RS showing that ROR2-RS was closely clustered with other gene forms of the syndrome (Zhang et al, 2022).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The phenotypes are ordered by dendrogram shown on the left based on hierarchical agglomerative clustering (HAC) analysis. A prevalence key is provided on the right This is in accordance with our recent phenotypic analysis of dominant RS showing that ROR2-RS was closely clustered with other gene forms of the syndrome (Zhang et al, 2022).…”
Section: Discussionsupporting
confidence: 83%
“…The identification of the causative genes in RS further illuminated the underlying patho‐mechanism of disease and enhanced the understanding of how the molecular lesions lead to the phenotypic expression. The molecular diagnosis together with quantitative deep phenotyping using Human Phenotype Ontology (HPO) terms and similarity analysis have recently become powerful tools for delineating disease contributing molecular pathways, the biology of disease, and the definition of the etiology of many syndromes, including RS (Zhang et al, 2022). A detailed phenotypic characterization of patients with an identified disease causing variant allele allows more precise genotype–phenotype correlation, delineation of allele‐specific phenotypic differences, and increases the accuracy of clinical diagnosis and management.…”
Section: Introductionmentioning
confidence: 99%
“…Additional W548* and G434V variants were reported by White et al (17) and Warren et al (11) in patients with AD-RS and ADO. White et al (17) also identified G434S and W377* variants, and Zhang et al reported another three related individuals with the W548* variant as well as a F130Cfs*98 variant and G434S (18). Due to the highly overlapping phenotypes seen in patients classified with ADO and AD-RS, there has been some confusion as to how patients with FZD2-related skeletal phenotypes should be classified.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the highly overlapping phenotypes seen in patients classified with ADO and AD-RS, there has been some confusion as to how patients with FZD2-related skeletal phenotypes should be classified. Zhang et al performed a Human Phenotype Ontology analysis for 16 subjects with FZD2 variants and concluded all FZD2 patients grouped with patients that had known variants in other genes associated with Robinow syndrome (18). They suggested that patients with Fzd2 variants that result in characteristic limb shortening and craniofacial malformations be classified as FZD2-associated AD-RS.…”
Section: Introductionmentioning
confidence: 99%
“…For NXN , what was perhaps most interesting was a patient outlier who combined an SNV with an ~1 Mb deletion CNV in 17p13.3. Also the most common non‐RS phenotype in the cohort was four patients with FDG1 variants associated with Aarskog–Scott syndrome (AAS; MIM #305400) that clustered together within the differential diagnosis cluster quantitatively showing the remarkable clinical phenotype overlap (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%